Deep River : A Memoir of a Missouri Farm - Hamilton, David, 1939 June 9- (Book collections on Project MUSE., 2001)
It is land with a long history of occupation and use, extending millennia before the Missouris. Most recently it was briefly and intensively receptive to farming before being restored in large part as state-managed wetlands." "Deep River is composed of four sections, each exploring aspects of the farm and its neighborhood. While the family story remains central to each, slavery and the Civil War in the nineteenth century and Native American history in the centuries before that become major themes as well. The resulting portrait is both personal memoir and informal history, brought up from layers of time, the compound of which forms an emblematic American story."--Jacket.